Range extension of endemic butterflies in Western Mindanao, Philippines - Abijay, Leizel Mae R.; Badon, Jade Aster T.; Nuñeza, Olga M.; Maceda, Justin N. (2023)
A recent assessment on the butterflies of Mount Gutom, Zamboanga del Norte, Mindanao,
Philippines, resulted in range extensions of Mindanao endemic nymphalid butterflies such as
Zethera hestioides and Zethera musa.